Profitability Indicators: Critical Analysis and Applicability in Modern Conditions - S. A. Bondarenko; S. V. Pupentsova (Управленческие науки, 2024)
Constant variability of the external environment is one of the key features affecting the business activity of domestic organizations and generates the need for constant updating of managers’ professional skills. The issues of assessment efficiency of commercial companies are always relevant not only for owners, but also for managers, employees and other stakeholders. In the conditions of economic instability, the interest to the indicators of organizations’ efficiency increases and, accordingly, their clarification and adjustment is required. and adjustment. The purpose of the study is to summarize the profitability indicators depending on the goal-setting of the participants of commercial organizations and to establish the possibility of using these indicators to assess the effectiveness of the company’s activities. Many years of experience of the authors of this article in the field of business valuation allowed to systematize the techniques of calculation of the main profitability indicators, to present an updated system of their grouping, as well as to classify the factors affecting them. Also, theoretical approaches to the calculation of invested capital were generalized in the course of the work. The research applied the methods of analysis, comparison, synthesis, classification, collection and generalization, logic, graphical and tabular display of information. Theoretical significance of the obtained results consists in the development of the methodology of value-oriented management in order to actualize and adapt the algorithms for calculating profitability indicators to domestic conditions, taking into account the interests of the participants of the organization. The practical significance of the work consists in the development of methods for assessing the performance indicators of the company, which can be used in the corporate governance of commercial structures, as well as in making management decisions by stakeholders.